2020
DOI: 10.35848/1347-4065/ab6d85
|View full text |Cite
|
Sign up to set email alerts
|

Mobility enhancement by mechanical uniaxial stress on 4H-SiC (0001) lateral metal-oxide-semiconductor field-effect-transistor

Abstract: We investigated the impact of the mechanical uniaxial strain on the inversion channel mobility of lateral n-channel metal-oxide-semiconductor field-effect transistor (MOSFET) on 4H-SiC(0001). We used custom-designed bend-holders to apply a tensile and compressive stress to the chip after MOSFET fabrication. The behavior of mobility with the two different channel directions and was investigated on the bend directions and with the tensile and compressive stress. We found that the inversion channel mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…It has also been predicted theoretically that stress can improve the mobility for SiC [24], [25]. Further, there is experimental literature showing improved mobility with externally applied strain in SiC planar MOSFETs [26], [27]. However, the kind of strain inducing enhancements that are standard in Si CMOS have not been integrated into SiC transistor structures so far.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been predicted theoretically that stress can improve the mobility for SiC [24], [25]. Further, there is experimental literature showing improved mobility with externally applied strain in SiC planar MOSFETs [26], [27]. However, the kind of strain inducing enhancements that are standard in Si CMOS have not been integrated into SiC transistor structures so far.…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be noted that the uniaxial strain induced by this bending method is not the same kind as the expected strain in mass production devices; however, this method has its own advantage for excluding other variables and showing stress' solo impact on the device. 15) In this study, we will describe a quantitative relationship between uniaxial stress and device performance, focusing on field-effect mobility (μ FE ) and V th , and discuss the origins of the variability of device performance with stress.…”
mentioning
confidence: 99%
“…The channel direction was along. [11][12][13][14][15][16][17][18][19][20] The MOS interface was passivated by a conventional nitridation process with nitric oxide (NO) gas after the growth of 38 nm thick oxide. A Si (100) n-MOSFET with 8 nm thick oxide and channel along [110] was used for electrical characteristics comparison and stress evaluation based on a clear relationship between the ratio of the change in peak field-effect mobility ( FE m D ) and applied stress established on Si n-MOSFETs.…”
mentioning
confidence: 99%
“…They have reported that compressive stress improves mobility due to lighter effective mass. 23,24) However, the tensile stress on 4H-SiC has not received much attention.…”
mentioning
confidence: 99%
“…Here, we limit the discussion on the strain below 0.5% since experiments have reported sub-GPa stress in SiC interface. 21,23) The first and second conduction band minima for 4H-SiC are located at point M of the Brillouin zone. Although the biaxial stress was applied, the crystal symmetry in the (0001)plane did not change when the surface was in the c plane [(0001) plane].…”
mentioning
confidence: 99%